التفسير بالمأثور عند المدرسة العقلية الحديثة - حمد، جنان سليمان (Kulliyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2005)
This study examines the attitude of the modern intellectual school towards the different transmitted methods of exegesis from both theoretical and applied perspectives, and attempts to analyze the factors that influenced this attitude. It also aims at summing up the features and theoretical fundamentals on which this attitude is based. The study adopted the inductive and analytical methods to trace the views of the school’s promoters, examine a set of applied cases, and highlight the influencing factors behind the attitude of the school concerned. It also employed the historical approach to understand the circumstances and challenges that led to this school from towards the transmitted exegesis. The critical and comparative approaches were also employed, the former to diagnose the drawbacks of this position, and the latter to balance and compare the various views of its drawbacks. The study arrived at a number of findings that may be briefly summarized below. There are a number of factors that triggered the cautious and alter attitude of this school towards transmitted exegesis, however, without totally and out rightly rejecting, or belittling it. This is particularly reflected in its often disregard, reservation, re-interpretation or shelving of a sizable part of the transmitted exegesis for reasons that are mainly related to its critique of the texts of the transmitted exegesis and not its fundamentals. The most important of these reasons are that the transmitted exegesis is presumably not explicitly doctrinal, similar to deviant Israelite narration, contradicting with the Bible, founded on a form of superstition, based on accusation against the messengers, established on prophecies that may lead to reliance, or incompatible, from the scholars’ point of view, with the norms and interest of the time.